2004
DOI: 10.1074/jbc.m405079200
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Restriction Allows cAMP Activation of the B-Raf/ERK Pathway, Switching Cells to a cAMP-dependent Growth-stimulated Phenotype

Abstract: cAMP can be either mitogenic or anti-mitogenic, depending on the cell type. We demonstrated previously that cAMP inhibited the proliferation of normal renal epithelial cells and stimulated the proliferation of cells derived from the cysts of polycystic kidney disease (PKD) patients. The protein products of the genes causing PKD, polycystin-1 and polycystin-2, are thought to regulate intracellular calcium levels, suggesting that abnormal polycystin function may affect calcium signaling and thus cause a switch t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
311
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 318 publications
(329 citation statements)
references
References 74 publications
12
311
0
1
Order By: Relevance
“…Our data suggest that the high biological activity of B-Raf V600E cannot be directly inhibited by compounds interfering with Ras activation or S446 phosphorylation and that the development of therapies for tumours harbouring a BRAF V600E allele should focus on the inhibition of the catalytic centre or expression of B-Raf. However, still to be developed S446 kinase inhibitors might be useful for the treatment of pathologies that are dependent on B-Raf signals but contain BRAF wt alleles, for example, tumours overexpressing B-Raf wt or harbouring activating mutations of upstream activators such as Ras or receptor tyrosine kinases, or polycystic kidney disease, which is characterized by increased B-Raf activation (Tanami et al, 2004;Yamaguchi et al, 2004). Similarly, S446 kinase inhibitors might be useful to attenuate the activity of other clinically relevant non-V600E B-Raf mutants.…”
Section: Regulation Of B-raf Signallingmentioning
confidence: 99%
“…Our data suggest that the high biological activity of B-Raf V600E cannot be directly inhibited by compounds interfering with Ras activation or S446 phosphorylation and that the development of therapies for tumours harbouring a BRAF V600E allele should focus on the inhibition of the catalytic centre or expression of B-Raf. However, still to be developed S446 kinase inhibitors might be useful for the treatment of pathologies that are dependent on B-Raf signals but contain BRAF wt alleles, for example, tumours overexpressing B-Raf wt or harbouring activating mutations of upstream activators such as Ras or receptor tyrosine kinases, or polycystic kidney disease, which is characterized by increased B-Raf activation (Tanami et al, 2004;Yamaguchi et al, 2004). Similarly, S446 kinase inhibitors might be useful to attenuate the activity of other clinically relevant non-V600E B-Raf mutants.…”
Section: Regulation Of B-raf Signallingmentioning
confidence: 99%
“…The cellular damage is secondary to a chain of biochemical and biologic abnormalities. 16,17 An abnormal proliferative response of ADPKD cells to cAMP has been reported, apparently associated with defective intracellular Ca 2Ï© homeostasis, 18 and animal models of PKD have been associated with dysregulated cell-cycle activity. 19 Piontek et al, 20 however, have shown that the effects of Pkd1 inactivation in mice are determined by a developmental switch on postnatal day 13.…”
mentioning
confidence: 99%
“…The clinical relevance of understanding their interactions is most obvious in the change in ERK1/2 regulation by cAMP in polycystic kidney disease (PKD) [51,52]. PKD is often caused by loss of polycystin 1 or 2.…”
Section: Signaling Imbalances and The Potential Role Of Erk1/2 In Polmentioning
confidence: 99%
“…In normal kidney, ERK1/2 support growth inhibition in response to elevated cAMP. In PKD, ERK1/2 appear to induce proliferation in response to elevated cAMP, which results in the formation of cysts and loss of epithelial polarity [51,56]. Inhibition of the ERK1/2 pathway decreases abnormal proliferation.…”
Section: Signaling Imbalances and The Potential Role Of Erk1/2 In Polmentioning
confidence: 99%
See 1 more Smart Citation